Metabolic diseases. Supporting content for Biochemistry. - María de Jesús Sánchez Bouza; Maricel Castellanos González; Pedro Sánchez Frenes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
-